Perhydropolysilazane resins and methods for their preparation
By controlling the silicon-nitrogen ratio to 1–1.5, the problems of volume shrinkage and residual stress in polysilazane resins were solved, enabling the preparation and widespread application of high-performance resins.
Patent Information
- Application Number
- CN202311037001.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-08-16
AI Technical Summary
Existing polysilazane resins suffer from high volume shrinkage and high residual stress during processing, which affects their performance and service life.
A fully hydrogenated polysilazane resin is provided, wherein the ratio of silicon atoms to nitrogen atoms in the main structural unit is Si/N=1 to 1.5. The fully hydrogenated polysilazane resin is prepared by mixing trichlorosilane prepolymer and dichlorosilane prepolymer under a nitrogen atmosphere and carrying out a polymerization reaction under the action of a catalyst.
It significantly reduces resin volume shrinkage and residual stress, and has comprehensive properties such as environmental friendliness and high temperature resistance. The preparation process is simple and easy to scale up, making it suitable for coatings, coatings, protection, adhesives, ceramic precursors and composite materials.
Smart Images

Figure CN116854920B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and more specifically, to a perhydropolysilazane resin and its preparation method. Background Technology
[0002] Polysilazane flame retardants are a class of polymeric resin materials with Si-N bonds as the main chain and organic groups as side chains. Silicon and nitrogen atoms are arranged alternately to form the basic framework, with the molecular formula [R1R2Si-NR3]. n The structure forms cyclic and linear polymers, which have excellent comprehensive properties such as high temperature resistance, corrosion resistance, weather resistance, hydrophobicity and antifouling. They are often used in high temperature resistant rubber and composite materials.
[0003] In recent years, the potential applications of polysilazane flame retardants in coatings, protective coatings, adhesives, and ceramic precursors have been gradually discovered. However, during processing, the density of polysilazane resin increases due to curing and cross-linking, leading to volume shrinkage and residual stress within the resin. Because these resins have poor toughness, high residual stress can cause defects such as cracks, affecting the performance and service life of polysilazane resins and their composites. Therefore, how to suppress the shrinkage of polysilazane resins and reduce their residual stress has become an urgent problem to be solved in related fields. Summary of the Invention
[0004] The main objective of this invention is to provide a fully hydrogenated polysilazane resin and its preparation method, so as to solve the problems of high shrinkage and large residual stress of polysilazane resin in the prior art.
[0005] To achieve the above objectives, according to one aspect of the present invention, a perhydropolysilazane resin is provided, the main structural unit of which is Furthermore, the ratio of silicon atoms to nitrogen atoms is Si / N = 1 to 1.5.
[0006] Furthermore, the ratio of silicon atoms to nitrogen atoms in the perhydropolysilazane resin is Si / N = 1.3 to 1.5; preferably, the weight-average molecular weight of the perhydropolysilazane resin is 800 to 9600.
[0007] According to another aspect of the present invention, a method for preparing the above-mentioned all-hydrogen polysilazane resin is also provided, wherein trichlorosilane prepolymer and dichlorosilane prepolymer are mixed under a nitrogen atmosphere and polymerized under the action of a catalyst to obtain all-hydrogen polysilazane resin.
[0008] Further, the preparation method includes the following steps: S1, under a nitrogen atmosphere, trichlorosilane prepolymer and dichlorosilane prepolymer are mixed and stirred to form a reaction system; S2, a catalyst is added to the reaction system and the polymerization reaction is carried out by continuous stirring to obtain a perhydropolysilazane resin.
[0009] Furthermore, the weight ratio between the trichlorosilane prepolymer and the dichlorosilane prepolymer is (0.4–0.9):1.
[0010] Furthermore, the weight-average molecular weight of the trichlorosilane prepolymer is 200–1500, and the weight-average molecular weight of the dichlorosilane prepolymer is 500–2000.
[0011] Further, in step S1, after the trichlorosilane prepolymer and dichlorosilane prepolymer are mixed, they are stirred at a temperature of -35 to -15°C to form the reaction system.
[0012] Furthermore, in step S2, the polymerization temperature is -35 to -15°C, and the reaction time is 3 to 8 hours.
[0013] Furthermore, the catalyst is selected from diallylamine and / or alkyl tertiary amines; preferably, the alkyl tertiary amine is selected from one or more of trioctyl tertiary amine, dodecyl tertiary amine, monoocta-tertiary amine, and monodeca-tertiary amine.
[0014] Furthermore, the amount of catalyst added is 2 to 12% of the total weight of the trichlorosilane prepolymer and the dichlorosilane prepolymer.
[0015] This invention provides a perhydropolysilazane resin having structural units. Furthermore, the silicon to nitrogen atom ratio is Si / N = 1 to 1.5. This all-hydrogen polysilazane resin can improve the problems of volume shrinkage and residual stress in polysilazane resins. In addition, it also has comprehensive properties such as environmental friendliness and high temperature resistance, and the preparation process is simple, the reaction conditions are easy to control, the equipment investment is low, and it is easy to scale up production. Moreover, the polysilazane resin of this invention is a liquid and can be used alone or in combination with other materials in coatings, coatings, protection, adhesives, ceramic precursors, composite materials and other fields, showing great development potential. Attached Figure Description
[0016] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0017] Figure 1 The proton NMR spectrum of the all-hydrogen polysilazane liquid prepared according to Example 1 of the present invention is shown. Detailed Implementation
[0018] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0019] As described in the background section of this invention, the high shrinkage rate and large residual stress of existing polysilazane resins limit their applications. To address these problems, this invention provides a perhydropolysilazane resin, the main structural unit of which is... Furthermore, the ratio of silicon atoms to nitrogen atoms is Si / N = 1 to 1.5.
[0020] This invention provides a perhydrosilazane resin with a silicon to nitrogen atom ratio of Si / N = 1 to 1.5, which significantly improves the problems of volume shrinkage and residual stress in polysilazane resins. In addition, it possesses comprehensive properties such as environmental friendliness, strong adhesion, high temperature resistance, corrosion resistance, and good weather resistance. Furthermore, the preparation process is simple, reaction conditions are easy to control, equipment investment is low, and it is easy to scale up production. Moreover, the polysilazane resin of this invention is a liquid and can be used alone or in combination with other materials in coatings, coatings, protective coatings, adhesives, ceramic precursors, composite materials, and other fields, showing great development potential.
[0021] The silicon to nitrogen atom ratio (Si / N) mentioned above includes, but is not limited to, 1.05:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, and 1.5:1. To further improve the above-mentioned properties of the perhydropolysilazane resin, in a preferred embodiment, the silicon to nitrogen atom ratio in the perhydropolysilazane resin is Si / N = 1.3 to 1.5; more preferably, Si / N = 1.35 to 1.42; preferably, the weight-average molecular weight of the perhydropolysilazane resin is 800 to 9600.
[0022] According to another aspect of the present invention, a method for preparing the above-mentioned all-hydrogen polysilazane resin is also provided, comprising: mixing trichlorosilane prepolymer and dichlorosilane prepolymer under a nitrogen atmosphere and carrying out a polymerization reaction under the action of a catalyst to obtain all-hydrogen polysilazane resin.
[0023] The above method is simple to prepare, the reaction conditions are easy to control, the equipment investment is low, and it is easy to scale up production. Moreover, the prepared all-hydrogen polysilazane resin has less volume shrinkage and residual stress, and its overall performance is better. Its property is liquid, and it can be used alone or in combination with other materials in coatings, coatings, protection, adhesives, ceramic precursors, composite materials and other fields, which has great development prospects.
[0024] To make the reaction process more stable, in a preferred embodiment, the above preparation method includes the following steps: S1, under a nitrogen atmosphere, trichlorosilane prepolymer and dichlorosilane prepolymer are mixed and stirred to form a reaction system; S2, a catalyst is added to the reaction system and the polymerization reaction is carried out by continuous stirring to obtain a perhydropolysilazane resin.
[0025] By adjusting the feeding ratio of the two prepolymers, the ratio of silicon atoms to nitrogen atoms in the synthesized all-hydrogen polysilazane resin can be controlled. Preferably, the weight ratio between the trichlorosilane prepolymer and the dichlorosilane prepolymer is (0.4-0.9):1, including but not limited to 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, and 0.9:1. To make the silicon-nitrogen ratio more suitable and thus further improve the product performance, the weight ratio between the above-mentioned trichlorosilane prepolymer and dichlorosilane prepolymer is more preferably (0.6-0.9):1.
[0026] In a preferred embodiment, the weight-average molecular weight of the trichlorosilane prepolymer is 200–1500, and the weight-average molecular weight of the dichlorosilane prepolymer is 500–2000. Selecting prepolymers with these weight-average molecular weights for polymerization to prepare perhydropolysilazane resins results in a more stable and controllable reaction process, and the prepared product has a more suitable silicon-nitrogen atom ratio and better performance. Specifically, the trichlorosilane prepolymer can be obtained by ammonolysis of trichlorosilane for 2–8 hours, and the dichlorosilane prepolymer can be obtained by ammonolysis of dichlorosilane for 2–8 hours.
[0027] In a preferred embodiment, in step S1 above, after the trichlorosilane prepolymer and dichlorosilane prepolymer are mixed, they are stirred at a temperature of -35 to -15°C to form the reaction system. More preferably, in step S2 above, the polymerization reaction temperature is -35 to -15°C, and the reaction time is 3 to 8 hours. Controlling the temperature conditions at each stage within the above range can better maintain the stability and efficiency of the reaction system, and after the above reaction time period, the resulting product has a more suitable molecular weight and the reaction is more complete. Most preferably, the polymerization reaction temperature is -20°C, and the reaction time is 4 to 6 hours.
[0028] To further improve reaction efficiency, in a preferred embodiment, the catalyst is selected from diallylamine and / or alkyl tertiary amines; preferably, the alkyl tertiary amine is selected from one or more of trioctyl tertiary amine, dodecyl tertiary amine, monoocta-tertiary amine, and monodeca-tertiary amine. Most preferably, the catalyst is diallylamine.
[0029] In order to improve reaction efficiency and avoid waste of raw materials, in a preferred embodiment, the amount of the catalyst added is 5 to 10% of the total weight of the trichlorosilane prepolymer and the dichlorosilane prepolymer.
[0030] In summary, the present invention has the following beneficial effects:
[0031] 1. Unlike existing polysilazane resins, the present invention provides a perhydropolysilazane resin with a silicon to nitrogen atom ratio between 1 and 1.5, which can minimize the volume shrinkage and residual stress of the perhydropolysilazane resin.
[0032] 2. This invention, through a designed synthetic route, polymerizes trichlorosilane prepolymers and dichlorosilane prepolymers under the action of a catalyst to obtain perhydropolysilazane. The preparation process is simple, the reaction conditions are easy to control, the equipment investment is low, and it is easy to scale up production. Furthermore, the synthesized perhydropolysilazane resin is a liquid and can be used alone or in combination with other materials in coatings, coatings, protective coatings, adhesives, ceramic precursors, composite materials, and other fields, showing great development potential.
[0033] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0034] Example 1
[0035] The preparation method of the all-hydrogenated polysilazane resin is as follows:
[0036] A trichlorosilane prepolymer with a weight-average molecular weight of 1000 and a dichlorosilane prepolymer with a weight-average molecular weight of 1500 were fed at a mass ratio of 0.46:1 and stirred evenly at -25°C. Then, diallylamine catalyst (5% of the total weight of the two prepolymers) was added to the reaction system, and the mixture was stirred continuously while maintaining the low temperature for 4 hours to obtain a fully hydrogenated polysilazane liquid. Its proton NMR spectrum is shown below. Figure 1 .
[0037] The prepared perhydropolysilazane was coated onto a silicon wafer using a 0.2 mm thin film coater and allowed to cure completely at room temperature for 5 hours. The ratio of silicon to nitrogen atoms in the perhydropolysilazane was determined using a Pelletron 3SDH apparatus via Rutherford backscattering method. The results showed that the ratio of silicon to nitrogen atoms (Si / N) in the synthesized perhydropolysilazane resin was approximately 1.05.
[0038] The prepared all-hydrogen polysilazane resin film was heat-treated under a nitrogen atmosphere: after treatment at 200°C for 2 hours, it was then treated at 850°C for 1 hour. The shrinkage rate and residual stress of the resin were then tested.
[0039] Shrinkage rate calculation: Shrinkage rate = (L1 - L2) / L1 × 100
[0040] L1 represents the film thickness after treatment at 200℃ for 2 hours, and L2 represents the film thickness after treatment at 850℃ for 1 hour. The thicknesses were measured using a reflective molecular film thickness gauge. Based on testing and calculation, the shrinkage rate of this all-hydrogen polysilazane resin is approximately 15%.
[0041] Method for determining residual stress: A silicon wafer coated with a perhydropolysilazane resin film was bent, and its radius of curvature was measured using a Tencor FLX-2320 to calculate the stress value. The residual stress of the perhydropolysilazane resin was tested to be approximately 16 MPa.
[0042] Furthermore, when the all-hydrogen polysilazane resin of Example 1 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0043] Example 2
[0044] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the trichlorosilane prepolymer and dichlorosilane prepolymer are fed in a mass ratio of 0.9, and the other preparation process is the same as that in Example 1.
[0045] Tests showed that the silicon to nitrogen ratio (Si / N) of the all-hydrogen polysilazane resin was approximately 1.42, the shrinkage rate was approximately 7%, and the residual stress was approximately 8 MPa.
[0046] Furthermore, when the all-hydrogen polysilazane resin of Example 2 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0047] Example 3
[0048] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the trichlorosilane prepolymer and dichlorosilane prepolymer are fed in a mass ratio of 0.6, and the other preparation process is the same as that in Example 1.
[0049] Tests showed that the silicon to nitrogen ratio (Si / N) of the all-hydrogen polysilazane resin was approximately 1.35, the shrinkage rate was approximately 12%, and the residual stress was approximately 13 MPa.
[0050] Furthermore, when the all-hydrogen polysilazane resin of Example 3 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0051] Example 4
[0052] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the trichlorosilane prepolymer and dichlorosilane prepolymer are fed in a mass ratio of 0.85, and the other preparation process is the same as that in Example 1.
[0053] Tests showed that the ratio of silicon atoms to nitrogen atoms (Si / N) in the all-hydrogen polysilazane resin was approximately 1.5, the shrinkage rate was approximately 6%, and the residual stress was approximately 7 MPa.
[0054] Furthermore, when the all-hydrogen polysilazane resin of Example 4 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0055] Example 5
[0056] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the trichlorosilane prepolymer and dichlorosilane prepolymer are fed in a mass ratio of 0.55, and the other preparation process is the same as that in Example 1.
[0057] Tests showed that the ratio of silicon atoms to nitrogen atoms (Si / N) in the all-hydrogen polysilazane resin was approximately 1.3, the shrinkage rate was approximately 13%, and the residual stress was approximately 14 MPa.
[0058] Furthermore, when the all-hydrogen polysilazane resin of Example 5 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0059] Example 6
[0060] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the trichlorosilane prepolymer and dichlorosilane prepolymer are fed in a mass ratio of 0.4, and the other preparation process is the same as that in Example 1.
[0061] Tests showed that the ratio of silicon atoms to nitrogen atoms (Si / N) in the all-hydrogen polysilazane resin was approximately 1, the shrinkage rate was approximately 16%, and the residual stress was approximately 17 MPa.
[0062] Furthermore, when the all-hydrogen polysilazane resin of Example 6 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0063] Example 7
[0064] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the weight average molecular weight of the trichlorosilane prepolymer is 1500 and the weight average molecular weight of the dichlorosilane prepolymer is 2000.
[0065] Tests showed that the ratio of silicon atoms to nitrogen atoms (Si / N) in the all-hydrogen polysilazane resin was approximately 1.2, the shrinkage rate was approximately 12%, and the residual stress was approximately 13 MPa.
[0066] Furthermore, when the all-hydrogen polysilazane resin of Example 7 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0067] Example 8
[0068] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the weight average molecular weight of the trichlorosilane prepolymer is 200 and the weight average molecular weight of the dichlorosilane prepolymer is 500.
[0069] Tests showed that the silicon to nitrogen ratio (Si / N) of the all-hydrogen polysilazane resin was approximately 1.01, the shrinkage rate was approximately 17%, and the residual stress was approximately 18 MPa.
[0070] Furthermore, when the all-hydrogen polysilazane resin of Example 8 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0071] Example 9
[0072] The perhydropolysilazane resin is basically the same as that in Example 1, except that the catalyst is dodecylamine.
[0073] Tests showed that the silicon to nitrogen ratio (Si / N) of the all-hydrogen polysilazane resin was approximately 1.055, the shrinkage rate was approximately 15%, and the residual stress was approximately 16 MPa.
[0074] Furthermore, when the all-hydrogen polysilazane resin of Example 9 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0075] Example 10
[0076] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that the catalyst is a mono-octa-tert-amine.
[0077] Tests showed that the silicon to nitrogen ratio (Si / N) of the all-hydrogen polysilazane resin was approximately 1.045, the shrinkage rate was approximately 15%, and the residual stress was approximately 16 MPa.
[0078] Furthermore, when the all-hydrogen polysilazane resin of Example 10 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0079] Example 11
[0080] The all-hydrogen polysilazane resin is basically the same as that in Example 1, except that: the amount of catalyst used is 10% of the total weight of the two prepolymers, the system temperature and polymerization temperature are both -20°C, and the reaction time is 6h.
[0081] Tests showed that the ratio of silicon atoms to nitrogen atoms (Si / N) in the all-hydrogen polysilazane resin was approximately 1.3, the shrinkage rate was approximately 13%, and the residual stress was approximately 14 MPa.
[0082] Furthermore, when the all-hydrogen polysilazane resin of Example 11 was tested at 1600°C in an air-filled tube furnace, no decomposition was observed, indicating that the synthesized all-hydrogen polysilazane resin can withstand high temperatures above 1500°C.
[0083] For ease of comparison and analysis, the Si / N ratio, shrinkage rate and residual stress of the all-hydrogen polysilazanes obtained in Examples 1 to 11 are statistically shown in Table 1.
[0084] Table 1
[0085]
[0086] Comparative examples show that changes in the ratio of trichlorosilane prepolymer to dichlorosilane prepolymer lead to changes in the ratio of silicon to nitrogen atoms in the synthesized perhydropolysilazane resin. Under appropriate monomer ratios, perhydropolysilazane resins with lower shrinkage and residual stress can be obtained.
[0087] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a perhydropolysilazane resin, characterized in that, The preparation method includes the following steps: S1, under a nitrogen atmosphere, trichlorosilane prepolymer and dichlorosilane prepolymer are mixed and stirred to form the reaction system; S2, the catalyst is added to the reaction system, and the polymerization reaction is carried out by continuous stirring to obtain the all-hydrogen polysilazane resin; The weight ratio between the trichlorosilane prepolymer and the dichlorosilane prepolymer is (0.4~0.9):1; the weight-average molecular weight of the trichlorosilane prepolymer is 200~1500, and the weight-average molecular weight of the dichlorosilane prepolymer is 500~2000. The polymerization reaction is carried out at a temperature of -35 to -15°C for 3 to 8 hours. The catalyst is selected from diallylamine and / or alkyl tertiary amines, wherein the alkyl tertiary amine is selected from one or more of trioctyl tertiary amine, dodecyl tertiary amine, monoocta-tertiary amine, and monodeca-tertiary amine. The amount of catalyst added is 2 to 12% of the total weight of the trichlorosilane prepolymer and the dichlorosilane prepolymer. The main structural unit of the all-hydrogen polysilazane resin is Furthermore, the ratio of silicon atoms to nitrogen atoms is Si / N = 1~1.
5.
2. The method for preparing the all-hydrogenated polysilazane resin according to claim 1, characterized in that, In step S1, after the trichlorosilane prepolymer and the dichlorosilane prepolymer are mixed, they are stirred at a temperature of -35~-15℃ to form the reaction system.
3. The method for preparing the all-hydrogenated polysilazane resin according to claim 1, characterized in that, The ratio of silicon atoms to nitrogen atoms in the all-hydrogen polysilazane resin is Si / N = 1.3~1.
5.
4. The method for preparing the all-hydrogenated polysilazane resin according to claim 1, characterized in that, The weight-average molecular weight of the perhydropolysilazane resin is 800-9600.
Citation Information
Patent Citations
Inorganic polysilazane resin
CN104114483A
N-h free and si-rich perhydridopolysilzane compositions, their synthesis, and applications
CN110023235A
